2022
DOI: 10.1103/physrevlett.129.124501
|View full text |Cite
|
Sign up to set email alerts
|

Eulerian vs Lagrangian Irreversibility in an Experimental Turbulent Swirling Flow

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…It is an asymmetrical vorticity filament, with exponential vorticity profile corresponding to a Burgers vortex. Further investigation using time-resolved numerical [44] or experimental measurements [46] actually showed that the most irregular situations are obtained during vortex interaction, as illustrated in Figure 5b. More refined analysis prove that the interaction corresponds to vortex reconnection [47].…”
Section: Observation Of Most Irregular Structurementioning
confidence: 94%
“…It is an asymmetrical vorticity filament, with exponential vorticity profile corresponding to a Burgers vortex. Further investigation using time-resolved numerical [44] or experimental measurements [46] actually showed that the most irregular situations are obtained during vortex interaction, as illustrated in Figure 5b. More refined analysis prove that the interaction corresponds to vortex reconnection [47].…”
Section: Observation Of Most Irregular Structurementioning
confidence: 94%
“…This property prescribes the 'arrow-of-time' of the irreversible Navier-Stokes dynamics and it is plausible that a similar property carries over to dissipative weak Euler solutions obtained in the inviscid limit (Eyink 2006). The dissipative anomaly for Navier-Stokes turbulence may be characterised also in terms of the time asymmetry of separation of stochastic Lagrangian particle (Drivas 2019;Cheminet et al 2022), which in three dimensions separate faster backwards in time than they do forwards in time (Eyink 2011;Buaria et al 2016).…”
Section: Origin Of Singularitiesmentioning
confidence: 85%
“…The dissipative anomaly for Navier–Stokes turbulence may be characterised also in terms of the time asymmetry of separation of stochastic Lagrangian particle (Drivas 2019; Cheminet et al. 2022), which in three dimensions separate faster backwards in time than they do forwards in time (Eyink 2011; Buaria et al. 2016).…”
Section: Turbulence Away From Wallsmentioning
confidence: 99%
“…Finally, by the experiments by Meneveau and Sreenivasan [39][40][41], assuming their flows remain bounded with increasing Reynolds number, the dimension of support of anomalous dissipation is 0.87 above our lower bound, indicating that -unlike the simple shock singularities and mathematical constructions -incompressible turbulence does not sit at the lower threshold of our theorem. It would be interesting to obtain additional experimental and numerical measurements of the spacetime support of the dissipation, perhaps leveraging a Lagrangian interpretation [5,12].…”
Section: Theorem 12 (Incompressible Euler)mentioning
confidence: 99%